Hybrid towers: How can the pandemic improve mixed-use way of living? - Pather, Kyle Cameron (My University, 2022)
The need to remain at home under quarantine due to the outbreak of Covid-19, as well as its impact on inhabitants' mental well-being, should be a hot topic among architects and planners. Many of us have had to negotiate dining room tables, kitchen counter-tops, and sofas with our partners, children, and pets as a result of Covid-19. Our living areas might start feeling too small or too gloomy, with no way to focus or unwind. While quarantine was intended to have been a preventative measure against the spread of the virus, studies have shown that it had detrimental psychological impacts on many individuals especially those who live in apartment environments, and a part of this research seeks to understand why. Together with the aim of addressing overall mental well-being in mixed-use buildings during quarantine and looking into the factors that regulate a healthy home in the fields of mental health and architecture. We are not capable of remaining in these environments for extended periods of time, as being confined in a cold concrete room for extensive periods is shown to inflict mental depression among tower residents. This virus has shown us that it's vital to develop adaptable, fluid, and integrated spaces with opportunities for human engagement. In the post-pandemic era, the places where we congregate will be even more significant. They will become spaces of engagement and interaction, rather than places of exile and/or separation. Despite the overwhelming support that mixed-use development has received, it is not universally accepted. Mix-used buildings were created with the goal of cramming as many people as possible into a small space; health and well-being were not taken into account. Our homes have evolved into more than just a refuge from monotony and daily chaos; they now serve as a safe haven from viruses and other threats. They have evolved into our new work-play-live environment; however, a physical boundary needs to be formulated as well as a mental one. Developments are being constructed across the country to serve citizens and commercial clients, as developers and designers strive to create more eco-friendly homes. In the design sector, more inventive and innovative building approaches are becoming popular and gaining traction because a structure must be living, growing and evolving over time in accordance with its foundation and surroundings. As a result, hybrid design has resurfaced as a proposal to improve the living quality of apartment occupants in the future. This study suggests a hybrid eco-system that combines public and private activities while also enhancing habitat conditions and regenerating the surrounding communities. Furthermore, utilizing a Mass Timber structural approach to design a residential tower and explore how post-covid designing adaptable spaces may contribute to the development of a Hybrid Bio-philic mixedused development. My primary goal is to bring attention towards a more efficient alternative for conventional construction by emphasizing on making our spaces and places healthier and safer through optimal design while applying one innovative building approach, Hybrid construction.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, 2022